Cu6Sn5 and Cu3Sn lntermetallics Study in the Sn-40Pb/Cu System during Long-term Aging - Mayappan, Ramani; Ahmad, Zainal Arifin (Scientific Research Journal, 2010)
Replacing Sn-Pb solder with lead-free solder is a great challenge in the electronics industry. The presented lead-free solder is Sn based and forms two intermetallic species upon reaction with the Cu substrate, namely Cu6Sn5 and Cu3Sn. The growth of Cu6Sn5 and Cu3Sn intermetallics have been investigated with respect to Sn-40Pb/Cu solder joints. The joints were aged under long-term thermal exposure using single shear lap joints and the intermetallics were observed using scanning electron microscopy. As-soldered solder joints exhibit a single Cu6Sn5 phase, however after aging a Cu3Sn layer below the Cu6Sn5 is observed to manifest. The Cu6Sn5 layer develops with a scalloped morphology, whereas the Cu in layer always develops an undulating planar shape in phase with the Cu6Sn5. The Cu6Sn5 layer begins to transform from a scalloped- to a planar-shape as aging progresses in order to minimize the interfacial energy. The intermetallic layers exhibit a linear dependence on the square root of aging time, which corresponds to diffusion-controlled growth. The activation energy for the growth of the Cu6Sn5 intermetallic layer has been determined to be 56.16 kJ/mol.